Early symbolic comprehension of a digital image as a source of information and as a mean of communication - Jauck, Daniela; Peralta, Olga (Anales de Psicología / Annals of Psychology, 2016)
Graphs, photographs, digital images, are very much present in children´s lives from very early, accomplishing a variety of functions. In this research we explore the symbolic comprehension of a digital image provided by a Tablet as a mean of communication and as a source of information by 24-month-old children. We used two tasks. In the first, children had to indicate in the image the localization where they have observed the experimenter hid the toy in a small room. In the second, children had to search for an object in the room guided by the image in which the experimenter indicated the location where the object was hidden. We found that children utilized the image as a source of information to guide their search, but not as a mean of communication to inform the localization to someone else. However, after a brief experience in the utilization of the image as a source of information, children successfully used it as a mean of communication. The results show that for young children using the image of the Tablet as a source of information not only is simpler but also has facilitating effects in its use as a mean of communication.